(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the outcomes of sentinel lymph node imaging and biopsy using the Technetium-99m (Tc-99m) radioisotope in patients with early-stage breast cancer and to analyze factors associated with axillary lymph node metastasis. Subjects and Methods: A retrospective descriptive study was conducted on 55 patients with early-stage breast cancer treated at the Department of Breast Surgery, K Hospital, from June 2021 to September 2021. Patients underwent sentinel lymph node imaging using Tc-99m and sentinel lymph node biopsy during surgery, followed by comparison with the histopathological results of axillary lymph node dissection specimens. Evaluated indicators included the sentinel lymph node detection rate, number of sentinel lymph nodes identified, rate of sentinel lymph node metastasis, and analysis of factors associated with lymph node metastasis. Results: The sentinel lymph node detection rate was 96.4%. The mean number of sentinel lymph nodes identified was 1.8 ± 0.6 nodes per patient. The sentinel lymph node metastasis rate was 23.6%. The sensitivity of sentinel lymph node biopsy was 92.3%, while specificity reached 100%. No severe complications related to the technique were recorded. Factors associated with axillary lymph node metastasis included histopathological type (p < 0.05), histological grade (p < 0.05), and lymphovascular invasion (LVI) status (p < 0.05). Conclusion: Sentinel lymph node biopsy using Tc-99m is a safe, feasible, and highly accurate method for evaluating axillary lymph node status in patients with early-stage breast cancer. This technique contributes to reducing unnecessary axillary lymph node dissection and minimizing postoperative complications.